ANTERIOR TALOFIBULAR LIGAMENT (ATFL) RECONSRUCTION WITH MODIFIED BROSTROM-GOULD TECHNIQUE USING FIBER WIRE - Andre Triadi Desnantyo; Mouli Edward; Asyumaredha Asyumaredha (Journal Orthopaedi and Traumatology Surabaya, 2019)
Background: The incident of ankle sprain reported 1 of 10.000 case each day. The most incident was male about 22-24 year and sport active. We reported 2 cases (15 years old female and 21 years old male) both of them played routine basketball and futsal.Case: We reported 2 cases, male 21 years old and female 15 years old, both of them suffered from anterior talofibular ligament rupture, with AOFAS score fair (below 80 point) from the MRI there is rupture of ATFL.Discussion: The patient administered to the hospital after injury at sport. By physical examination (fair at AOFAS score) and radiological finding, they was decided underwent rupture anterior talofibular ligament and prepared for reconstruction with modified Brostrom-Gould technique using fiber wire. After + 3 month, the evaluation from physical diagnostic, radiology and we got an excellent AOFAS score, which means the 2 patient got really satisfaction and has no limitation at doing daily activities.Conclusion: ATFL is one of the lateral ligament of the ankle which protect the foot while moving at plantar flexion. Modified Brostrom-Gould technique using fiber wire gave good result for reconstruction ATFL rupture for these 2 patients.